Acute zonal occult outer retinopathy (AZOOR) complex associated with torpedo retinopathy following COVID-19 recombinant mRNA vaccination: a case report of a rare clinical presentation - Nai-Wen Chang; Chia-hao Kuo; Hung-Da Chou; Yi-Hsing Chen (BMC Ophthalmology)
Abstract Background While vaccination remains crucial in mitigating the impact of the COVID-19 pandemic, several ocular adverse events has been reported, including Acute Zonal Occult Outer Retinopathy (AZOOR) complex. Case presentation A 31-year-old female presented declined best corrected visual acuity (BCVA) and flashes in both eyes three days following second recombinant mRNA COVID-19 vaccine (Moderna). Fundus autofluorescence (FAF) illustrated speckled hyper-AF lesions surrounding right eye torpedo maculopathy site and hyper-AF lesions in the left macula. The spectral-domain optical coherence tomography delineated inner and outer segment (IS/OS) line disruption; hyperreflective deposits in the outer nuclear layer (ONL); and undetectable interdigitation zone (IDZ). Her BCVA further declined after 3-month observation, thus she received 8-month oral prednisolone and mycophenolate mofetil treatment. Her BCVA recovered; the hype-AF lesions resolved; and the IS/OS line and ONL resumed. Conclusions We present a rare case of AZOOR complex following COVID-19 vaccination inciting from torpedo retinopathy where outer-retinal barrier breaks down.